The Role of Teachers in Shaping Students' Character through Enforcement of Discipline and Habituation in Madrasah - Ali Yakub; Rumbang Sirojudin; Hunainah Hunainah; Eti Shobariyah (Universitas Muhammadiyah Enrekang, 2025)
This research aims to examine the role of teachers in shaping student character through rules enforcement and habituation at madrasah. Using a qualitative approach with descriptive methods, data were collected through observation, interviews, and documentation at Madrasah Tsanawiyah in Banten Province. The results showed that rules enforcement provided clear behavioral guidelines fostering discipline and responsibility, while habituation established positive behavioral patterns such as honesty and cooperation. Teachers acted not only as enforcers but also as role models implementing humanistic approaches. Integration of both strategies effectively shaped students’ moral character aligned with Islamic values. It is recommended that madrasah enhance teacher training on character education integration to maximize these approaches in daily practice.